SOSIALISASI SUMBER ENERGI LIMBAH SEBAGAI PEMBUATAN KOMPOR BIOMASSA DI KELOMPOK IKATAN KELUARGA EKA KENCANA KEC. MEDAN JOHOR - Sari Novalianda; Syafrida Hanum Hutasuhut (Jurnal Abdi Ilmu, 2020)
During this time of the corona pandemic, many businesses experienced a decrease in income. This has an impact on the income that housewives earn. They complain about the increasing cost of household needs. Seeing the location in the eka kencana group, Medan johor sub-district, there is a lot of waste that can be used to use biomass energy to become a biomass stove. For this reason, the technology offered by socialization uses a biomass stove with insulation walls with a closed system, where the wood burning process is carried out in a room free from the influence of environmental air gusts. The method used in this activity is the socialization method for partner communities about the use of waste as an energy source for biomass stoves. The result of this activity is that the community can understand about the use of waste as an energy source for making biomass stoves to save expenses during the corona pandemic and take advantage of the surrounding waste and harm the local environment.